Analisis Metode Failure Mode and Effect Analysis (FMEA) dan Fault Tree Analysis (FTA) Untuk Identifikasi Penurunan Kualitas Produk Toyota Hi-Ace (Studi Kasus di PT. EDS Manufacturing Indonesia) - Lestari, Sri; Septiyana, Diah; Yuniawati, Winda (UNISTEK, 2021)
The high level failure is a problem that company always to minimized and to improve quality of final products, and also were conducted by PT. EDS Manufacturing Indonesia (PEMI) which is consistent in producting a quality product. PT. EDS Manufacturing Indonesia (PEMI) manufacture Toyota HI-ACE carline product for motorcycle. Therefore the high level failure in this product is unacceptable because it can harm or kill company, then to solve this problem we propose to use Failure Mode and Effect Analysis (FMEA) method and Fault Tree Analysis (FTA). Our research using the FMEA method at PT. EDS Manufacturing Indonesia for Toyota HI-ACE carline product shows the existence of various modes of failure in the production and quality assurance areas. The FMEA method give suggestions for improvements to the 2 failure modes to be priority based on the highest RPN value that is wrong dimension and demage insulation. The next step is identify the risks that contribute to failure with using the Fault Tree Analysis (FTA). With FMEA we found the highest RPN value that show highest defect such as damage insulation 324 or 14.78% and wrong dimension 280 or 12.77%. Keywords: failure mode, risk analysis, FMEA, FTA, RPN Value